Effectiveness of Feedback on Continuous Assessment: Students’ Views - Sankaran, Suguna; Low, Suet Fin (Asian Journal of Assessment in Teaching and Learning, 2025)
Feedback is a crucial component of the learning process, particularly in the realm of continuous assessment, where it serves to enhance student understanding, guide improvement, and foster engagement. This study examined the effectiveness of feedback mechanisms within the context of continuous assessment from the viewpoint of students. Through a cross-sectional study employing quantitative methods, data were collected from a diverse sample of students enrolled at the Institute of Teacher Education Malaysia under the Bachelor of Teaching Degree Preparation Program (PPISMP), Bachelor of Teaching Degree Program (PISMP), and Postgraduate Diploma in Education Program (PDPP). The findings highlighted that most students have a very positive perception of lecturers’ feedback on continuous assessment. Many students valued constructive feedback as a catalyst for future improvement, while a small number expressed concerns regarding the consistency and usefulness of feedback provided by instructors. Additionally, the findings provided vital insights for lecturers to use as guidelines in giving feedback on students’ continuous assessments. Overall, this study underscored the importance of soliciting and integrating students’ views in the design and implementation of feedback mechanisms within continuous assessment frameworks, thereby optimizing learning outcomes and promoting student engagement and satisfaction.